Effect of Temperature on Synthesis of Hydroxyapatite/Chitosan Composite Using the In-Situ Method as a Heavy Metal Adsorbent - Jamarun, Novesar; Amirullah, Tri Yupi; Syukri, Syukri; Prasejati, Arika; Wulandari, Wulandari; Caniago, Sintia; Tricahyani, Nabiila Ayyu (Indonesian Journal of Chemistry, 2025)
Removing hazardous non-organic waste containing heavy metals like copper and lead is crucial for environmental protection. Adsorption offers a promising solution, with hydroxyapatite (HAp) serving as a biocompatible adsorbent due to its active surface area. However, its mechanical limitations necessitate enhancement through compositing with chitosan (CTS), a natural biopolymer. This study synthesized hydroxyapatite from cuttlefish bone as a calcium source, while chitosan was extracted from shrimp shells. The hydroxyapatite/chitosan (HAp/CTS) composites were prepared in situ at varying temperatures (55, 60, 65, 70, and 75 °C). The composites were characterized using FTIR, XRD, SEM, and SAA. The result indicated successful integration of HAp and CTS, with a crystallite size of 13.82 nm in the 65 °C composite. Based on SEM-EDS analysis, the HAp/CTS 65 °C morphology was agglomerated chunk particles with a Ca/P ratio of 1.61. The highest adsorption capacity value is found in the HAp/CTS 65 °C composite for both ions, 1.9979 mg/g for Cu2+ ions and 0.9965 for Pb2+ ions. The reusability test results of the HAp/CTS 65 °C composite succeeded up to two cycles. This research proves that the adsorption of Cu2+ and Pb2+ ions by HAp/CTS composite adsorbent has been successfully carried out.